2017
DOI: 10.1103/physrevb.96.054420
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional magnetic phase separation in γ-CoV2O6

Abstract: We have explored the magnetism in the non-geometrically frustrated spin-chain system γ-CoV2O6 which possesses a complex magnetic exchange network. Our neutron diffraction patterns at low temperatures (T T N = 6.6 K) are best described by a model in which two magnetic phases coexist in a volume ratio 65(1) : 35(1), with each phase consisting of a single spin modulation. This model fits previous studies and our observations better than the model proposed by Lenertz et al in J. Phys. Chem. C 118, 13981 (2014), wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 39 publications
(80 reference statements)
4
17
0
Order By: Relevance
“…The k 1 phase disappears at T N1 = 6.6 K, while the Néel temperature of the k 2 phase (T N2 ) could not be unambiguously determined by NPD [13]. This is due to the prevailing magnetic diffuse scattering that emerges around the k 2 modulated Bragg positions above T and remains observable up to at least 25 K [13]. In the same region, another investigation, using magnetometry and inelastic neutron scattering (INS), has revealed strong ferromagnetic (FM) fluctuations in this compound [16].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The k 1 phase disappears at T N1 = 6.6 K, while the Néel temperature of the k 2 phase (T N2 ) could not be unambiguously determined by NPD [13]. This is due to the prevailing magnetic diffuse scattering that emerges around the k 2 modulated Bragg positions above T and remains observable up to at least 25 K [13]. In the same region, another investigation, using magnetometry and inelastic neutron scattering (INS), has revealed strong ferromagnetic (FM) fluctuations in this compound [16].…”
Section: Introductionmentioning
confidence: 94%
“…In the ground state, our neutron powder diffraction (NPD) study showed that γCVO possesses two spatially separated magnetic order modulated by k 1 = ( 1 2 , 0, 0) and k 2 = ( 1 4 , 0, -1 4 ), respectively [13,15]. As the temperature increases, the k 2 phase undergoes a commensurate-incommensurate transition at T = 5.6 K, accompanied by the loss of the long-range spin correlations [13]. The k 1 phase disappears at T N1 = 6.6 K, while the Néel temperature of the k 2 phase (T N2 ) could not be unambiguously determined by NPD [13].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations